ISOLATION AND PURIFICATION OF AVIDIN FROM EGG WHITE BY IMMOBILIZED METAL AFFINITY CHROMATOGRAPHY - Alwan Al-Mashikhi , Shalan (The Iraqi Journal of Veterinary Medicine, 1996)
Lysozyme and avidin were initially separated from egg white by cation exchange chromatography (Doulite C-464). Avidin was then isolated from lysozyme in pure form by immobilized metal affinity chromatography column (1.5 x 10cm) loaded with copper ions. The column was equilibrated with 0.02M phosphate buffer pH 7.7, containing 0.5M NaCl. Protein fraction obtained from Doulite column was applied on IMAC column, followed by washing with the starting buffer and eluting with pH gradient with 0.1M Acetic acid. Two peaks were obtained, the first peak represents the avidin, while the second peak represents the lysozyme as tested by SDS-PAGA and HABA assay. The purity of avidin was increased to 75% by the IMAC process.